EDZs and Firms’ Environment Performance: Empirical Evidence From Chinese Firms - Wei, Wei; Xie, Weikun; Zhou, Chengying (Frontiers in Environmental Science, 2022)
Economic Development Zones (EDZs) have been proved to be economic success and been pursued by many governments around the world over the past several decades, while there is still research gap in its impact on the environment. This paper documents the effect of national-level EDZs on environmental performance of firms. Combining rich firm and administrative data in China from 1998-2012, we exploit the relationship between foundation of EDZs and firms’ pollution emissions with multi-periods differences-in-differences (DID) model. We find that the establishment of national EDZs can effectively reduce pollution emission intensity of firms within it. Moreover, this pollution reduction effects vary across industries, firms and EDZs types. We also find that the establishment of EDZs can improve firm environmental performance by improving energy efficiency, optimizing business environment and upgrading technology.